2020
DOI: 10.54589/aol.33/3/200
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment related to arterial stiffness in cardiovascular disease patients with severe periodontitis

Abstract: Severe periodontal disease (SPD) associated with systemic peripheral inflammation, cognitive impairment (CI) and arterial stiffness (AS) has been recognized. The aim of this study was to investigate whether CI and arterial stiffness (AS) occur in cardiovascular disease (CVD) patients with SPD. A crosssectional case-control study included hospitalized patients with CVD. Demographic characteristics, CVD and atherogenic risk factors were recorded. SPD was diagnosed by clinical and radiographic dental examinations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The same research found no differences in catalase levels between groups. 60 Lipid peroxidation (LPO) is an important consequence of oxidative stress that can be evaluated by measuring MDA. Nguyen et al 58 performed a study in which they divided patients into 4 groups: ACS + periodontitis, ACS only, periodontitis only, and healthy controls.…”
Section: Acute Coronary Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…The same research found no differences in catalase levels between groups. 60 Lipid peroxidation (LPO) is an important consequence of oxidative stress that can be evaluated by measuring MDA. Nguyen et al 58 performed a study in which they divided patients into 4 groups: ACS + periodontitis, ACS only, periodontitis only, and healthy controls.…”
Section: Acute Coronary Syndromementioning
confidence: 99%
“…58,59 The intensity of oxidative stress can be assessed by measuring the oxygenation rate of various molecules or the activity of antioxidant enzymes (e.g., catalase). A study by Rubio et al 60 revealed higher levels of salivary dichlorodihydrofluorescein diacetate (DCFH-DA) oxidation rates in ACS patients compared with controls. The same research found no differences in catalase levels between groups.…”
Section: Cardiovascular Diseases and The Clinical Utility Of Saliva A...mentioning
confidence: 99%
“…Periodontitis is the primary cause of tooth loss in adults. It can destroy the supporting tissues of the teeth and influence systemic health [ 4 ].…”
Section: Introductionmentioning
confidence: 99%